Analisis Program Hafiz Quran TPQ - Noni Hutami; Muhammad Sahid Almadini (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Hafiz Quran Program at Al-Quran Education Park (TPQ) is an important initiative in Efforts to increase the interest in reading and understanding of Muslims towards the holy book. This research Aims to analyze the effectiveness of the Hafiz Quran program in TPQ, with a focus on Teaching methods, level of student achievement, as well as their impact on development Character. The method used in this research is a qualitative approach and Data collection through interviews, observations, and documentation studies. Results from research This shows that the program is not only successful in improving the ability Reading or memorizing Al-Quran, but also greatly contributes to the formation of morals And santri character. Interactive and fun teaching methods, as well as support from Competent teachers, become a determining factor in the success of the program. Other than that, there is Challenges in maintaining student motivation, especially in the long term. This research recommends the need for a more varied curriculum development and Training for teachers to overcome these challenges. Thus, the Hafiz program Quran in TPQ is expected to continue to contribute positively in the formation of a generation that Loves Al-Quran and has a good character.